STANDARDIZATION THE SYSTEM OF ASSESSMENT FOR COMPETENCE AND RELATED OBJECTS BASED ON THE STANDARD ISO/IEC 24763 - Michael V. Levin; Sergey E. Sosenushkin (Открытое образование (Москва))
The article considers the main statements of the international standard ISO/IEC 24763, that defines the requirements to the competency framework and to the competency information management, description, evaluation and merging methods in different IT-systems. The necessity for competency evaluation IT-systems development is considered in terms of advanced staff training, creating e-portfolios and career development.